Role of Surfactants and Their Applications in Structured Nanosized Systems - Matiacevich, S (Springer, 2015)
In this chapter, the role of surfactants and their applications in structured nanosized systems are reviewed, including nanoemulsions, nanoliposomes, solid lipid nanocarriers (SLNs) and nanostructured lipid carriers (NLC). In addition, to cover the technical aspects of these topics, understanding of the molecular interactions to assemble nanosized systems, the structural design principles and the most used surfactants in the food industry are also discussed. Finally, a theoretical mathematical model to determine the optimal value of surfactant concentration is presented. © Springer Science + Business Media New York 2015.
Keywords: Emulsifiers; Multilayer emulsions; Multiple emulsions; Nanoliposomes; Nanosized systems; Nanostructured lipid carriers; Solid lipid nanocarriers; Surfactants